INDIVIDUALIZED SURGICAL STRATEGY IN INFECTED PANCREATIC NECROSIS WITH DIABETES - Hakimov, D.M.; Kasimov, N.A. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
Infected pancreatic necrosis (IPN) is one of the most severe and life-threatening complications of acute necrotizing pancreatitis. In patients with diabetes mellitus, the clinical course of IPN is aggravated by immune dysfunction, microvascular complications, and metabolic instability. Traditional surgical approaches often fail to account for the individual variability in disease progression, infection severity, and patient resilience. This review aims to provide an overview of current literature on the role of personalized surgical strategies in the management of IPN in diabetic patients. Emphasis is placed on early risk stratification, imaging-based staging, timing and modality of intervention, and perioperative glycemic control. Advances in minimally invasive necrosectomy, step-up approaches, and multidisciplinary decision-making are discussed in the context of diabetic physiology. The need for individualized treatment algorithms that integrate clinical, biochemical, and radiological data is highlighted as a cornerstone of modern surgical practice in IPN.